2002
DOI: 10.1182/blood-2002-05-1511
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the hemangioblast in postnatal life

Abstract: Postnatal CD34 ؉ cells expressing vascular endothelial growth factor receptor 2 (KDR) generate hematopoietic or endothelial progeny in different in vitro and in vivo assays. Hypothetically, CD34 ؉ KDR ؉ cells may comprise hemangioblasts bipotent for both lineages. This hypothesis is consistent with 2 series of experiments. In the first series, in clonogenic culture permissive for hematopoietic and endothelial cell growth, CD34 ؉ KDR ؉ cells generate large hematoendothelial (Hem-End) colonies (5% of seeded cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
174
2
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(187 citation statements)
references
References 21 publications
5
174
2
6
Order By: Relevance
“…This region appears to consist of hemangioblast-like cells because CD34 and KDR were also positive in addition to nestin (Figure 2b and c). 13 We examined the cell proliferative features of this region using two proliferation markers; PCNA and Ki-67. PCNA-positive nuclei were distributed in numerous cells in this microcapillary region ( Figure 2e), whereas Ki-67-positive cells were few and limited mostly to the microcapillary endothelia (Figure 2f).…”
Section: Nestin Expression In Hemangioblastomasmentioning
confidence: 99%
See 1 more Smart Citation
“…This region appears to consist of hemangioblast-like cells because CD34 and KDR were also positive in addition to nestin (Figure 2b and c). 13 We examined the cell proliferative features of this region using two proliferation markers; PCNA and Ki-67. PCNA-positive nuclei were distributed in numerous cells in this microcapillary region ( Figure 2e), whereas Ki-67-positive cells were few and limited mostly to the microcapillary endothelia (Figure 2f).…”
Section: Nestin Expression In Hemangioblastomasmentioning
confidence: 99%
“…12 Hemangioblasts are characterized by the hematopoietic marker proteins CD34, and VEGF receptor type 2 (also called Flt-1, or KDR). 12,13 In tumor angiogenesis, bone marrow-derived endothelial progenitor cells contribute much to newly forming angiogenic vessels. 12,14 Thus, in the angiogenic endothelium of tumors, a significant number of hemangioblast-like hematopoietic precursor cells may be integrated in the endothelial cell population.…”
mentioning
confidence: 99%
“…5,13,21,23,24 Many different stem cell populations, including bone marrow (BM) mononuclear cells, AC133 ϩ endothelial progenitor cells, and embryonic stem cells have the potential to differentiate in vitro and in vivo into mature and functional ECs. 4,[25][26][27][28] We have recently described another stem cell population, multipotent adult progenitor cells (MAPCs), that differentiates into most somatic cell types, including functional ECs, in vitro and in vivo. [29][30][31][32][33] The question of whether and how these stem cells can be coaxed into arterial or venous ECs has thus far not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, postnatal CD34 þ KDR þ cells comprise hemangioblasts, endowed with bipotent hematopoietic and endothelial differentiation capacity. 19 In line with these findings, adult murine VEGF (À/À) cells show a sharp depletion of the HSC pool: importantly, treatment with VEGF mutants revealed that activation of KDR is sufficient to rescue the HSC activity. 20 Specifically, KDR favors self-renewal and survival of primitive hematopoietic cells.…”
Section: Introductionmentioning
confidence: 59%